THE INFLUENCE OF SOCIAL MEDIA UTILIZATION ON SALES VOLUME IN CULINARY SMES IN MAKASSAR CITY - Annisa Wardhani Nur; Agus Syam; Valentino Aris (INJOSEDU: International Journal of Social and Education, 2025)
This research aims to analyze the impact of social media usage on sales volume in Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector in Makassar City. With the rapid development of technology and increasing internet penetration, social media has become an important platform for promoting products and attracting customers. This study uses a quantitative approach with a survey design, where data is collected through questionnaires distributed to owners and managers of culinary SMEs in Makassar. The variables analyzed include the intensity of social media usage, the types of social media platforms used, and the marketing strategies implemented through social media. The research results show that effective use of social media significantly impacts the increase in sales volume, with platforms like Instagram and Facebook contributing the most. These findings provide insights for culinary MSMEs to utilize social media as an effective marketing tool, while also enhancing their competitiveness and business sustainability.